2007
DOI: 10.1111/j.1574-695x.2006.00210.x
|View full text |Cite
|
Sign up to set email alerts
|

Borrelia burgdorferipotently activates bone marrow-derived conventional dendritic cells for production of IL-23 required for IL-17 release by T cells

Abstract: Lyme borreliosis is characterized by cellular inflammatory responses at multiple body sites. Recently, an association of interleukin-17 (IL-17) and Lyme arthritis was suggested. In this context, it is of special interest that the heterodimeric cytokine IL-23 can act on T cells and initiate the up-regulation of effector cytokines such as IL-17. To determine the role of this specific cytokine cascade for the induction of subsequently induced proinflammatory events we developed an in vitro system to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 66 publications
1
27
0
Order By: Relevance
“…It has been demonstrated that B. burgdorferi-induced IL-17 production in mice is dependent on IL-23 (19). Cells from mice lacking bioactive IL-23 (p19 deficiency) were unable to produce IL-17.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that B. burgdorferi-induced IL-17 production in mice is dependent on IL-23 (19). Cells from mice lacking bioactive IL-23 (p19 deficiency) were unable to produce IL-17.…”
Section: Discussionmentioning
confidence: 99%
“…However, this group did not show a dose-dependent induction of IL-23 production by B. burgdorferi species. So far, it was demonstrated only that murine bone marrow-derived dendritic cells (BMDCs) were able to produce IL-23 after exposure to B. burgdorferi species (19). In addition, human neutrophils were able to induce IL-23 after stimulation with neutrophil-activating protein A (NapA) isolated from B. burgdorferi (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In in vitro assay, B. burgdorferi induced IL-23 production by DC and IL-17 production by naive spleen cells (19). Since naive mouse-derived CD4 ϩ iNKT cells which lack expression of NK1.1 surface marker recognize BbGLIIc diacylglycolipid Ag from B.…”
Section: Role Of Il-17 In Immune Response Against Extracellular Bactementioning
confidence: 99%
“…Furthermore, neutralization of IL-17 causes substantial reduction of collagenase activity (33), osteoclast formation (83), and production of proinflammatory cytokines (1,32,77). Moreover, B. burgdorferi (82) or its lipoproteins (75) have been shown to induce the production of IL-17. These properties make the Th17 cell subset a strong candidate for an additional route by which Lyme arthritis may be induced.…”
Section: Lyme Arthritis: a Th1-mediated Response?mentioning
confidence: 99%